A Study the State and Approach of Guidance Activity Affair Management in School under the Secondary Educational Service Area Office 39 - Khanchai, Khatawut (Journal of Inclusive and Innovative Education, 2019)
The purposes of this research were to study the state and approach of guidance activity affair management in school under the secondary educational service area office 39. The sample in this research is School administrators and Teacher who work at of Guidance Activity under the secondary educational service area office 39 at the total of 114 respondents. Using the method by simple random sampling. The instrument used to collect the data was 5 level rating scale questionnaires. There are 51 items. The Index of item objective congruence was found to have an Index of item objective congruence ranging from 0.67 to 1.00. The reliability of the questionnaire was 0.99. The questionnaire used to collect data and analyzed by the mean, standard deviation and One-way analysis of variance. It found that; The state of school’s guidance activity affair management is on high level. Considering the guidance activity in descending order, 1) The educational guidance activity, 2) The career guidance activity, and 3) The personal and social guidance activity. Comparative Study of Guidance Activities of Educational Institutions Under the jurisdiction. School administrators and Teacher who work at of Guidance Activity that there was a statistically significant difference at .05 levels between the management of the school counseling activities and the size of the school. Educational institution of different sizes, there were no significant differences in the management of school counseling activities. The approach of school’s guidance activity affair management consists of 1) The educational guidance activity should increase the staff of educational counseling activities and schools should have asked student ideas for satisfaction. Students use the Educational Guidance Services. 2) The career guidance activity should add staff for career guidance activity; Educational institutions should assess weaknesses, strengths, problems and obstacles in career guidance activity. and 3) The personal and social guidance activity there should be teachers who have graduated in psychology, Schools should study the opinions and satisfaction of the learners using the personal and social counseling services.